Mycosis Fungoides, Then and Now… Have We Travelled?. (November 2015) - Mahalingam, Meera; Reddy, Vijaya B.
Abstract : Mycosis fungoides (MF) is the most common type of cutaneous lymphoma, accounting for almost 50% of all primary cutaneous lymphomas. When initially described, it was believed to be a distinct clinical entity with a pathognomonic histopathologic picture. Through the years we have come to know that, like syphilis, MF is a great masquerader and can present clinically and histopathologically in many ways. This review is an attempt to cover the many faces of MF that have evolved through the years.